FUNCTIONAL CONSTIPATION IN CHILDREN: QUESTIONS AND ANSWERS - V.F. Privorotskiy; N.E. Luppova (Вопросы современной педиатрии, 2008)
Key questions of pathogenesis, diagnostics and treatment of functional constipation in children are described in this article. Pediatrists have to pay a great attention to this problem, because quality of life of children is decreases very much due to constipation. A dramatic and typical clinical case of chronic constipation in patient, who was 6 years old, was reported. An algorithm of management of such patients is presented, but authors give attention to the fact, that oversimplified methods of treatment and monotherapy frequently can't provide positive results.Key words: children, functional constipation, diagnostics, treatment.